2018
DOI: 10.1007/s10549-018-4798-7
|View full text |Cite
|
Sign up to set email alerts
|

FFPE breast tumour blocks provide reliable sources of both germline and malignant DNA for investigation of genetic determinants of individual tumour responses to treatment

Abstract: BackgroundBio-banked formalin-fixed paraffin-embedded (FFPE) tissues provide an excellent opportunity for translational genomic research. Historically matched blood has not always been collected as a source of germline DNA. This project aimed to establish if normal FFPE breast tissue could be used as an alternative to blood.MethodsExome sequencing was carried out on matched tumour tissue, normal breast tissue and blood on five patients in the START trial. Retrieved samples had been archived at different centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Compared to fresh frozen tissue or blood samples, DNA samples isolated from FFPE tissue pose an analytical challenge, since the FFPE process usually leads to shorter DNA library insert sizes, and necessitates the generation of more DNA sequencing data. Although this leads to increased duplication rates and more variability in median coverage (Table 1 ), research has shown that FFPE samples do permit the reliable detection of genetic alterations, if sufficient sequence coverage can be obtained [ 31 , 32 ]. In this study, only four of 32 samples were excluded due to low sequencing depths, which is favourable compared to other WES studies of FFPE material [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to fresh frozen tissue or blood samples, DNA samples isolated from FFPE tissue pose an analytical challenge, since the FFPE process usually leads to shorter DNA library insert sizes, and necessitates the generation of more DNA sequencing data. Although this leads to increased duplication rates and more variability in median coverage (Table 1 ), research has shown that FFPE samples do permit the reliable detection of genetic alterations, if sufficient sequence coverage can be obtained [ 31 , 32 ]. In this study, only four of 32 samples were excluded due to low sequencing depths, which is favourable compared to other WES studies of FFPE material [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…51,52 The tumor site, together with the clinical nature of the two patient subsets, might have contributed to the difference observed in relative abundance. With regard to the use of FFPE samples, a recent study showed that FFPE tissues provide a reliable source of germline and malignant human DNA 53 ; therefore, it is expected that FFPE tissues also provide reliable bacterial DNA, 54 and an increasing number of researchers are undertaking metagenomics analyses using FFPE samples. 55,56 In conclusion, our exploratory analysis highlights that specific differences do exist in the tissue microbiome community between GISTs and benign lesions and that microbiome restructuring could drive the carcinogenesis process.…”
Section: F I G U R Ementioning
confidence: 99%
“…This could be in the context of research settings of high-risk populations and/or in families to obtain previously unavailable genetic information in deceased relatives to guide testing of surviving relatives. In other cancers (ovarian and breast cancer), studies validating archived tumor specimens for germline analysis have been performed (11,12).…”
Section: Analysis Of Archived Tumor Specimens For Hereditarymentioning
confidence: 99%